FAKTOR RISIKO PERILAKU MEROKOK PADA PEKERJA KONSTRUKSI DAN PEKERJA FISIK: SUATU TINJAUAN LITERATUR - Mahardhika, Adelia Putri (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2025)
Smoking behaviour among construction project workers is an underestimated occupational health problem, although this group is exposed to multiple interacting risk factors at the individual, work-related and social levels. Construction workers in Jakarta are predominantly male, of productive age, and work under physically demanding conditions, long working hours, exposure to dust and noise, and strict project deadlines, so that cigarettes are often used as a coping mechanism to deal with stress, fatigue and boredom. This literature study aims to identify risk factors associated with smoking behaviour among construction project workers, particularly in dense urban settings such as Jakarta. A Systematic Literature Review (SLR) approach was applied using the PRISMA 2020 guideline. Articles were searched through Google Scholar, accredited national occupational health journals and high-quality international journals, limited to publications between 2020 and 2025. The keywords used included “smoking behavior”, “construction workers”, “occupational stress”, “work fatigue”, “manual handling” and their Indonesian equivalents. Inclusion criteria were observational studies on construction project workers or similar manual labourers, addressing smoking behaviour and/or related risk factors, and available in full text. Twelve eligible articles were included and analysed narratively. The review shows that individual factors (sex, age, education, knowledge and attitudes about smoking, nutritional status and duration of smoking), job-related factors (type of occupation, physical workload, job stress, shift work, fatigue, manual handling) and social–organisational factors (social support, workplace smoking culture, easy access to cigarettes, and company policies) contribute to the high smoking prevalence among workers. Several studies also report health consequences such as hypertension, reduced appetite, chronic obstructive pulmonary disease, musculoskeletal complaints and work fatigue, which may impair productivity. In conclusion, smoking behaviour among construction project workers in urban areas should be understood as the result of multi-factor interactions, and tobacco control interventions need to be designed comprehensively through occupational health programs, smoke-free workplace policies and tailored cessation support at project sites.